Effect of interfacial surface treatment on bond strength of particulate-filled composite to short fiber-reinforced composite - L. Lassila; J. Tuokko; A. Suni; S. Garoushi; P. K. Vallittu (Medical Journals Sweden, 2022)
Objective The aim was to investigate the effect of different interfacial surface treatments on the shear bond strength (SBS) between a short fiber-reinforced flowable composite (SFRC) and a particulate-filled flowable composite (PFC). In addition, SBS between two successive layers of similar materials was evaluated.Materials and methods One-hundred and forty-four specimens were prepared having either SFRC (everX Flow) as a substructure composite and PFC (G-aenial Flo X) as a surface composite or having one of the two materials as both substructure and surface layer. Eight groups of specimens were created (n = 18/per group) according to the interfacial surface protocol used. Group 1: no treatment; Group 2: ethanol one wipe; Group 3: ethanol three wipes; Group 4: phosphoric acid etching + bonding agent; Group 5: hydrofluoric acid etching + bonding agent; and Group 6: grinding + phosphoric acid etching. Group 7: only PFC layers and Group 8 (control) only SFRC layers without any surface treatment. After one-day storage (37 °C), SBS between surface and substructure composite layers was measured in a universal testing machine, and failure modes were visually analyzed. SEM was used to examine the bonding surface of the SFRC composite after surface treatment. SBS values were statistically analyzed with a one-way analysis of variance (ANOVA) followed by the Tukey HSD test (α = .05).Results The SBS between successive SFRC layers (Group 8) was statistically (p < .05) the highest (43.7 MPa) among tested groups. Surface roughening by grinding followed by phosphoric acid etching (Group 6) resulted in a higher SBS (28.8 MPa) than the remaining surface treatments.Conclusion Flowable composite with glass fibers (everX Flow) showed higher interlayer SBS compared to PFC flowable composite. Interfacial surface roughness increases the bonding of PFC to the substructure of SFRC.